Chemical composition and radical scavenging activity of essential oil and methanolic extract of Eremostachys azerbaijanica Rech.f. from Iran - Solmaz Asnaashari; Fariba Heshmati Afshar; Atefeh Ebrahimi; Sedigheh Bamdad Moghadam; Abbas Delazar (Wolters Kluwer Medknow Publications, 2016)
In the present study, the chemical composition of the essential oil and methanol (MeOH) extract of aerials of E. azerbaijanica were identified. Furthermore, the free radical scavenging properties of the volatile oil as well as the MeOH extract of the plant were assessed. The essential oil of the air-dried aerial parts was obtained by hydro-distillation using a Clevenger-type apparatus. The oil was then analyzed by gas chromatography-mass spectrometry and gas chromatography with flame ionization detector. Soxhlet extraction was performed on the aerial parts using n-hexane, dichloromethane and MeOH. The MeOH extract was then subjected to solid-phase extraction using a C 18 Sep-Pak cartridge. Isolation and structural elucidation of the pure components was accomplished by high-performance liquid chromatography and spectroscopic methods (UV, 1 H-NMR). The free radical scavenging properties were determined by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. A total of 59 components representing 95.9% of the oil constituents were identified which were primarily characterized as terpenoids or aliphatic skeletons. The major components of the oil were hexahydrofarnesyl acetone (27.1%), 2-methyl-6-propyl-dodecane (16.4%) and tricosane (9.3%). One flavonoid (luteolin-7-O-rutinoside) and one phenylethanoid (verbascoside) were also isolated and identified from the MeOH extract. The results of DPPH assays showed that the essential oil of E. azerbaijanica possessed weak free radical scavenging activity whereas the MeOH extract and its pure constituents showed significant scavenging activities in comparison with positive controls.